Дополнительные сведения о блохах грызунов Днепропетровской области - Антоненко, В.В. (Вестник зоологии, 1969)
In 1961—62 in the Dnepropetrovsk region 1260 individuals of fleas were gathered from 396 rodents of 13 species and in 31 nests of seven rodent species. 1550 flea larvae were also found in the nests. The found fleas belong to 12 species 7 of which are mentioned for the first time for the Dniepropetrovsk region. They are: Ceratophyllus (Nosopsyllus) mokrzeckyi Wag n., C. (Monopsyllus) sciurorum S c h r., Ctenopthalmus agyrtes Hell., Ct. (Euctenophthal-mus) Magneri T і f l., Leptopsylla taschenbergi Wag n., L. (Peromyscopsylla) bidentota Koi., Hystrichopsylla talpae Curt. C. consimilis was dominating on (he rodents and Ct. orientalis — in the nests.